Novos insights sobre o uso de tomateiros anões para resistência a insetos-praga - Farias, Ana Karoline Silva Rocha de (2024)
ABSTRACT The tomato (Solanum lycopersicum L), belonging to the Solanaceae family, plays a role of considerable socioeconomic importance on a global scale. The increase in the presence of insect pests has caused considerable losses to producers. The investigation of cultivars that are more resistant to these insects has been the subject of study in genetic improvement programs, involving the introgression of resistance genes from wild tomato lines. There are gaps regarding the use of dwarf germplasm to confer resistance to pests, highlighting, in particular, the potential of the UFU MC TOM 1 lineage. The objective of the study was to select backcross populations from dwarf tomato plants for resistance to Tuta absolute (Meyrick, 1917) and Liriomyza huidobrensis (Blanchard, 1926), based on direct selection (injuries on leaves and leaflets) and indirect selection (acylsugar levels), aiming at a genetic background of interest. The experiment was conducted in 5L pots kept in a greenhouse, in a randomized block design (DBC), consisting of 20 treatments distributed in four blocks, totaling 80 plots. Seventeen populations were evaluated from the first, second and third backcrosses (BC1, BC2 and BC3), the donor parent UFU MC TOM 1, the recurrent parent UFU TOM 5 and the commercial hybrid cv. Vivacy. Analyzes were carried out to quantify the acylsugar levels, evaluate injuries to the plant and leaves and analyze herbivory using images. After the selection of interest, chromatographic analysis was carried out and the metabolomic profile was determined in the leaves of the donor parent UFU MC TOM 1. The population of dwarf plants UFU 13_1 shows promise for boosting genetic improvement programs, especially with regard to pest resistance. The progress achieved in generations of backcrossing resulted in significant variations in resistance levels, possibly influenced by genetic inheritance and the action of acylsugars. The UFU MC TOM 1 line, characterized by high levels of acylsugars, demonstrated consistent resistance to tomato moth and leaf miner in all evaluations conducted. Furthermore, in the leaves of this lineage, high expressions of metabolites such as glucose, lysine, myo-inositol and aspartic acid were identified. These findings open promising perspectives for future research aimed at resistance against various types of stresses, both biotic and abiotic. Keywords: Solanum lycopersicum L.; sustainable production; metabolomics; genetic improvement; antixenosis; insecta.